Measurement for Change: From Idea to Approach - van der Haar, Lotte; Holding, Penny A.; Krapels, Joachim; de Laat, Joost; Slemming, Wiedaad (Frontiers in Public Health, 2020)
Measurement for Change proposes an integration of monitoring, evaluation, and learning into decision-making systems that support sustainable transition of interventions to scale. It was developed using a cyclical, interactive one-year dialogue between early childhood development (ECD) practitioners and academics from across the globe. Details are presented in Krapels et al. (2020) as part of this special issue in Frontiers. In this paper, we trace the developments that inspired Measurement for Change and the novel ways in which the approach and the special issue was developed. The experience, and the reflections on this experience, are intended to inform those implementing initiatives that similarly seek to integrate practitioner- and academic experiences in support of sustainable transitions of interventions to scale.